Differences in Student Assertive Behavior in term of Gender - Tianda Hazmil Wibowo; Afdal Afdal (Jurnal Neo Konseling, 2019)
This research is motivated by the phenomenon of the number of students who are unable to behave assertively. The purpose of this study was to see the differences in assertive behavior of male and female students. This research is a type of quantitative research with a comparative descriptive method. The number of samples was 248 students of BK FIP UNP with proportional random sampling technique. The instrument of this study was a questionnaire about assertive behavior with a Likert scale model. Data were analyzed using the percentage formula and for differences in assertive behavior students with t-test techniques using SPSS version 20.00. The findings of this study indicate that (1) assertive behavior of students as a whole is in the moderate category with a percentage of 67.74% which expresses assertive behavior male students are higher than female students, (2) the results of the t-test state that there are differences significant with a significant level of 0.013. Based on the research, the counselor can help students with guidance and counseling services so that students have high assertive behavior.